Parietal lobe and disorganisation syndrome in schizophrenia and psychotic bipolar disorder: A bimodal connectivity study. (30th September 2020) - Das, Tushar K.; Kumar, Jyothika; Francis, Susan; Liddle, Peter F.; Palaniyappan, Lena
Highlights: We investigated structural and dynamic functional connectivity of the parietal lobe in schizophrenia and bipolar disorder with psychotic symptoms. Significant differences in left parietal structural connectivity and variability of left and right parietal dynamic functional connectivity between both patient groups and healthy controls. Parietal dysconnectivity predicted the severity of disorganisation symptoms in schizophrenia. Abstract: Given the emerging evidence in support of parietal brain stimulation to treat speech disorder in psychosis, we investigated structural and functional parietal dysconnectivity in schizophrenia ( n = 34) and bipolar disorder with psychotic symptoms ( n = 16). We found that both patient groups demonstrated reduced left parietal structural connectivity compared to healthy controls ( n = 32). The three groups also differed significantly on the variability of left and right parietal dynamic functional connectivity. In patients with schizophrenia, parietal dysconnectivity predicted the severity of disorganisation symptoms. These findings suggest that dysconnectivity between the parietal lobe and the rest of the brain plays a key role in disorganisation symptoms of schizophrenia.